Understanding pharmaceutical polymorphic transformations I: influence of process variables and storage conditions. (October 2014) - Sood, Jatin; Sapra, Bharti; Bhandari, Sameer; Jindal, Manish; Tiwary, Ashok K
The active pharmaceutical ingredient (API) of a dosage form is affected by number of mechanical and environmental factors which have a tendency to alter its crystalline state. Polymorphic transitions have been observed to occur during various unit operations like granulation, milling and compression. Forces of pressure, shear and temperature have an ability to induce alterations in crystal habit. A conversion in polymorphic form during a unit operation is very likely to affect the handling of API in the subsequent unit operation. Transitions have also been observed during storage of formulations where the relative humidity and temperature play a major role. An increase in temperature during storage can dehydrate or desolvate the crystal and hence produce crystal defects, whilst, high humidity conditions produce higher molecular mobility leading to either crystallization of API or alteration of its crystalline form.